ANÁLISE DE MANIFESTAÇÕES PATOLÓGICAS DE PÓS-OBRA EM FUNÇÃO DE SISTEMAS CONSTRUTIVOS DE EMPREENDIMENTOS IMOBILIÁRIOS - Barbosa, Ivan Carlos Alves; Picchi, Flavio A.; Granja, Ariovaldo Denis (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The strong growth in the housing market since 2008 has led companies to absorb labor without appropriate qualification. At the same time, the increase of the production pace to contractual compliance has invariably caused the loss of quality services. Among other effects, growing complaints from customers about perceived quality has occurred. The research aim was to analyze and organize the database of customers and end users recorded service and maintenance requests, specifically those related to pathological manifestations. The research also sought to classify the pathologies according to the employed building system, as well as to provide feedback to the design and engineering teams. A case study was carried out in a national real estate developer and data was collected from January 2014 to July 2017 for further processing and statistical analysis. The results suggest there is little divergencies in the top five pathologies found, despite regional variations in relation to the building systems used. The feedback of information to the design and engineering teams related may support preventive actions in relation to new pathological occurrences and strengthen quality delivery for customers and end users.